Visuo-Motor Affective Interplay: Bonding Scenes Promote Implicit Motor Pre-dispositions Associated With Social Grooming–A Pilot Study - Grichtchouk, Olga; Oliveira, Jose M.; Campagnoli, Rafaela R.; Franklin, Camila; Correa, Monica F.; Pereira, Mirtes G.; Vargas, Claudia D.; David, Isabel A.; Souza, Gabriela G. L.; Gleiser, Sonia; Keil, Andreas; Rocha-Rego, Vanessa; et al. (Frontiers in Psychology, 2022)
Proximity and interpersonal contact are prominent components of social connection. Giving affective touch to others is fundamental for human bonding. This brief report presents preliminary results from a pilot study. It explores if exposure to bonding scenes impacts the activity of specific muscles related to physical interaction. Fingers flexion is a very important component when performing most actions of affectionate contact. We explored the visuo-motor affective interplay by priming participants with bonding scenes and assessing the electromyographic activity of the fingers flexor muscle, in the absence of any overt movements. Photographs of dyads in social interaction and of the same dyads not interacting were employed. We examined the effects upon the electromyographical activity: (i) during the passive exposure to pictures, (ii) during picture offset and when expecting the signal to perform a fingers flexion task. Interacting dyads compared to matched non-interacting dyads increased electromyographic activity of the fingers flexor muscle in both contexts. Specific capture of visual bonding cues at the level of visual cortex had been described in the literature. Here we showed that the neural processing of visual bonding cues reaches the fingers flexor muscle. Besides, previous visualization of bonding cues enhanced background electromyographic activity during motor preparation to perform the fingers flexion task, which might reflect a sustained leakage of central motor activity downstream leading to increase in firing of the respective motor neurons. These data suggest, at the effector level, an implicit visuo-motor connection in which social interaction cues evoke intrinsic dispositions towards affectionate social behavior.